Respiratory Changes During Seed Germination. Histological Distribution of Respiratory Enzymes and Mobilization of Fat Reserves in Castor Bean Endosperm and Peanut Cotyledons - Castelfranco, Paul (1969)
Germinating peanut cotvledons and germinating castor bean endosperm have been compared with respect to their rates of fat dissimilation and with respect to the anatomical distribution of respiratory activity. The lipid mobilization is much slower in peanut cotyledons than in castor bean endosperm. Light has essentially no effect on either system. As germination progresses, the majority of the succinic dehydrogenase and cytochrome oxidase activities become localized in the vein regions of peanut cotyledons. In the castor bean endosperm these two activities are uniformly distributed throughout the storage parenchyma and increase with germination until the organ becomes soft and visibly senescent.